Ensuring low-cost generation and resource adequacy: The case of Pakistan's new Competitive Trading Bilateral Contract Market (CTBCM) model - Aksam Mukhtar (The Oxford Institute for Energy Studies, 2023)
Pakistan has a single-buyer market model, designed for centralized power procurement and investment in generation capacity. However, this model has encountered challenges in achieving both affordability and security of supply of electricity. A key contributing factor to the rise in electricity prices is the surge in capacity payments, which have more than doubled over the last five years. Pakistan has more recently introduced a new Competitive Trading Bilateral Contract Market (CTBCM) model to increase the competitiveness of its electricity market. This research study conducts an in-depth analysis of the capacity payment mechanism and its associated costs within Pakistan's electricity sector. Furthermore, they study critically evaluates the key features of the CTBCM model, assessing its potential to address the challenges of resource adequacy. The study also offers a comparative assessment of capacity costs and capacity remuneration mechanisms, which are implemented across several liberalized electricity markets. A case study of Pakistan's electricity market is modelled in detail to examine the potential impact of different market designs on energy and capacity prices. The research study has yielded several significant findings. First, Pakistani consumers bear an average capacity cost around four times than their counterparts in other markets, mainly because of elevated capital costs, the over-procurement of take-or-pay capacity contracts, and the inherent inefficiencies of the capacity payment mechanism. Furthermore, the evaluation of the CTBCM model suggests it has the potential to ensure resource adequacy but that the capacity obligation mechanism will elevate risks for distribution companies. Moreover, the Pakistan power market modelling indicates a projected decrease in short-run marginal costs under the government's capacity expansion plan, but capacity payments are expected to increase. A capacity market mechanism could reduce capacity costs by more than threefold compared with the capacity payment mechanism. However, the establishment of an energy market under the capacity market model is predicted to lead to a 42 per cent increase in overall electricity prices. The research study further establishes that the existing two-part tariff structure in a power purchase agreement-based market model does not promote competition and efficiency. Conversely, the energy and capacity market model, while leading to a short-term escalation in electricity prices, possesses the capability to employ price signals in determining optimal technology deployment, thus ensuring system-wide efficiency. Moreover, the paper presents a comprehensive framework that could assist in the design of a suitable capacity mechanism in Pakistan.
Keywords: 330; capacity market; case study; CTBCM model; electricity market; energy-only market; Pakistan; resource adequacy